Research on the Effective Application of Difficult Movements of Group C Jumps and Leaps in Competitive Aerobics Under the Guidance of Rules - Weiming Qiu (Studies in Social Science & Humanities, 2024)
Competitive aerobics is carried out in accordance with the current competition rules, the rules of each round of the period will undergo some changes, so the difficulty of group C jump and jump will also undergo some changes, in this case, if the athletes have the best understanding of the changes in the difficulty of the C group jump and jump, then the C group jump and jump difficulty action can be adjusted according to the actual combination of training and difficulty, in order to allow athletes to better adapt and improve their own level, so as to ensure and motivate the players to play on the field. This affects the performance of the players on the field. Based on this, based on the rule-oriented background, this paper analyzes the related problems related to the effective use of competitive aerobics C group jump and jump difficulty movements through the literature method, video analysis method and data statistics method, and draws the conclusion that the factors of female athletes in mixed doubles group C jump and jump difficulty are still the mainstream and the characteristic difficulty is more obvious, which provides a more efficient application method, a more efficient training direction and training content for the jump and jump difficulty of group C of competitive aerobics. Hopefully, it will be useful to reality.